Assessment of Interleukin-31 and Calprotectin in Immunocompromised Patients with Epstein-Barr Virus Infection - Rahim-Majid, Awat; Babakir-Mina, Muhammed (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Epstein-Barr virus (EBV) is among the most concerning herpesviruses, despite its typically asymptomatic or mildly self-limiting infections. The virus’s carcinogenic features and its ability to modulate the immune system are critical. That is why more research is needed on the hidden aspects of the virus’s life cycle, especially its oncogenic role and post-transplant complications. The study aims to harness EBV’s unique characteristics to gain new insights into its pathogenesis. This study was designed to investigate immunological and inflammatory biomarkers among three immunocompromised groups compared with an immunocompetent group in Sulaimani City (n = 81), including identification of EBV seropositivity in association with interleukin (IL) 31, calprotectin, lactate dehydrogenase, total leukocytes, granulocytes, lymphocytes, and platelets. EBV viral capsid antigen (VCA) immunoglobulin (Ig)M seropositivity was 29%, 21%, 15%, and 0%, in the immunocompetent, renal transplant, bone marrow transplant (BMT), and hematological malignancy groups, respectively. In addition, VCA IgM was inversely correlated with age (r = −0.353, p = 0.001). Interestingly, a significant association between the EBV VCA IgM index and IL-31, and, consequently, calprotectin levels, was observed. Regarding hematological parameters, the study found no significant association with EBV seropositivity. In conclusion, EBV latent Ig was less commonly recorded in the hematology and BMT groups than in the kidney transplant and immunocompetent groups. The findings suggest a possible association between IL-31 and calprotectin levels with EBV seropositivity; however, additional mechanistic studies are required to determine causality or oncogenic relevance.